Association of the oxytocin receptor gene with attitudinal trust: role of amygdala volume. Issue 10 (7th September 2018) - Nishina, Kuniyuki; Takagishi, Haruto; Fermin, A S R; Inoue-Murayama, Miho; Takahashi, Hidehiko; Sakagami, Masamichi; Yamagishi, Toshio
Abstract: Previous studies have shown that genetic variations in rs53576, a common variant of the oxytocin receptor gene ( OXTR ) resulting from a single nucleotide polymorphism involving an adenine (A)/guanine (G) transition, are associated with attitudinal trust in men. However, the pathway from gene to behaviour has not been elucidated. We conducted the present study to determine whether amygdala volume mediates the association between OXTR rs53576 genotypes and attitudinal trust. Our results revealed that the left amygdala volume was significantly smaller in GG men than in AA and AG men, whereas it was significantly smaller in AA and AG women than in GG women. In addition, the left amygdala volume was negatively associated with attitudinal trust in men, whereas there was no such association in women. We also found a significant mediation effect of the left amygdala volume on the association between OXTR rs53576 genotypes and attitudinal trust in men. The results of our study suggest that the left amygdala volume plays a pivotal role in the association between OXTR rs53576 genotypes and attitudinal trust in men.